Confucianism, Rule‐Consequentialism, and the Demands of Filial Obligations. Issue 2 (30th May 2019) - Sin, William
Abstract: Why should I take care of my aging parents? How far will morality require me to sacrifice for this cause? I will study these questions from the perspectives of Confucianism and rule‐consequentialism. Confucians believe that the continuity of families and the interactions between members of different generations can enhance the integrity of society in the long run. However, since Confucianism may impose extreme demands on its followers, this theory may be problematic. In this paper, I argue that despite its demands, the Confucian doctrines are defensible and are worth upholding. To explain my view, I draw upon rule‐consequentialism and explain how the rule‐consequentialist analysis complements and enhances the Confucian claims. I believe that the consequentialist conception of Confucianism can provide a useful resource for responding to the moral challenge of population aging in the current state of the world.